2016
DOI: 10.3390/ma9080704
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Effect Evaluation of Steel Fiber and Carbon Fiber on the Performance of the Fiber Reinforced Concrete

Abstract: Fiber reinforcement is an important method to enhance the performance of concrete. In this study, the compressive test and impact test were conducted, and then the hybrid effect between steel fiber (SF) and carbon fiber (CF) was evaluated by employing the hybrid effect index. Compressive toughness and impact toughness of steel fiber reinforced concrete (SFRC), carbon fiber reinforced concrete (CFRC) and hybrid fiber reinforced concrete (HFRC) were explored at steel fiber volume fraction 0.5%, 1%, 1.5% and carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…In 2016, Song and Yin have conducted the compressive test and impact test and then the hybrid effect between steel fiber (SF) and carbon fiber (CF) was evaluated by employing the hybrid effect index. Compressive toughness and impact toughness of SFRC), carbon fiber reinforced concrete (CFRC) and hybrid fiber reinforced concrete (HFRC) were explored at steel fiber volume fraction 0.5, 1, and 1.5%, and carbon fiber 0.1, 0.2, and 0.3%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2016, Song and Yin have conducted the compressive test and impact test and then the hybrid effect between steel fiber (SF) and carbon fiber (CF) was evaluated by employing the hybrid effect index. Compressive toughness and impact toughness of SFRC), carbon fiber reinforced concrete (CFRC) and hybrid fiber reinforced concrete (HFRC) were explored at steel fiber volume fraction 0.5, 1, and 1.5%, and carbon fiber 0.1, 0.2, and 0.3%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, low speed of hydration hindered the increasing trend in concrete strength and thus, presence of FA and GBFS left a negative impact on the speed of growth in strength although, they can improve the strength with respect to curing time [16]. In general, due to the glass texture of these two materials, as the alternative for cement, they can reduce the need for water to attain efficient workability for concrete [15,17,18]. Moreover, they benefited from a proper strength against chloride ions because of their small size by which durability could be improved [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Song and Yin [13] conducted compression and impact resistance tests on hybrid fiberreinforced concrete. They found that although the compressive strengths of steel and carbon fiber-reinforced concrete (CFRC) are improved, the improvement in the strength of the hybrid fiber-reinforced concrete is more significant.…”
Section: State Of the Artmentioning
confidence: 99%